The Participation of Oil Palm Growers ( Elaeis guineensis Jacq.) in Marketing Their Products at the Multi-Business Consumer Cooperative in Pematang Bandar District, Simalungun Regency - Nora, Silvia; Kamelia Noviyanti Saragih; Aisar Novita (Talenta Publisher, 2023)
This study aims to examine the level and factors that influence the participation of oil palm planters ( Elaeis guineensis Jacq.) in marketing their products at the Multi-Business Consumer Cooperative in Pematang Bandar District, Simalungun Regency. The research method used is quantitative research with a descriptive approach. The implementation of this study was carried out in Pematang Bandar District, Simalungun Regency, involving 54 respondents. Primary data includes the characteristics of farmers who are members of cooperatives and the results of questionnaires from the independent and dependent variables. The data was processed using multiple linear regression test. The results showed that the level of participation was categorized as very high with a value of 84.1% and the variables of service quality, welfare of extension workers, knowledge of cooperatives, interest in cooperatives and member satisfaction had a significant effect on the participation of smallholders. The variables of the role of the extension worker and the ability of the administrators have no significant effect.